Gene expression profiling indicates a shift in ammonia assimilation capacity along the hepatic acinus induced by different forms of selenium in vitamin–mineral mixes fed to beef steers grazing on toxic endophyte-infected tall fescue - Jia, Yang; Son, Kwangwon; Matthews, James C. (Frontiers in Animal Science, 2023)
Recently we demonstrated that supplementation (3 mg Se/day) of growing beef steers grazing Se-deficient toxic endophyte-infected tall fescue-based forage with either organic (OSe, SEL-PLEX) or a 1:1 blend (MIX) of OSe and inorganic Se (ISe, sodium selenite) vs. ISe forms of Se in vitamin-mineral mixes ameliorated several classic serum symptoms of fescue toxicosis. Importantly, MIX and OSe steers also had greater hepatic glutamine synthetase activity. Accordingly, transcriptome level and targeted mRNA expression analyses were conducted on the same liver tissue to determine if Se treatments affected other hepatic metabolic pathways, especially those responsible for supplying substrates of glutamine synthetase. The effect of ISe, OSe, and MIX treatments (n = 8/treatment) on the relative abundance of mRNA (microarray and real-time reverse-transcription PCR (RT-PCR)) and protein (Western blotting) in liver tissue was assessed by ANOVA. Fisher’s protected LSD procedure was used to separate treatment means, with significance declared if P ≤ 0.05. Microarray analysis identified (P < 0.01, false discovery rate of < 33%) 573 annotated differentially expressed gene (DEG) transcripts. Canonical pathway analysis identified DEG central to glutamine and glutamate biosynthesis/degradation and proline biosynthesis. Targeted RT-PCR analyses found that MIX and OSe vs. ISe steers had lesser periportal ammonia assimilation and urea-synthesizing capacity (lesser glutaminase 2, key ornithine cycle enzymes, and mitochondrial ornithine/citrulline exchanger mRNA). Concomitantly, MIX and OSe steers had a greater pericentral ammonia assimilation capacity (greater glutamine synthetase activity), and a greater capacity to make glutamate in pericentral hepatocytes from α-ketoglutarate (greater glutamine dehydrogenase, and decreased arginase 2 and ornithine aminotransferase, mRNA). The form of supplemental Se also affected hepatic proline metabolic capacity, with OSe steers having a greater capacity for proline synthesis and MIX steers having a greater capacity for pyrolline-5-carboxylate synthesis. In conclusion, supplementing MIX and OSe vs. ISe forms of Se in vitamin-mineral mixes of growing beef steers grazing toxic endophyte-infected tall fescue shifts hepatic ammonia assimilation from periportal urea production into pericentral glutamine production, thus potentially increasing whole-animal N efficiency by increasing the supply of hepatic-synthesized glutamine.